Pengaruh Kompos Kulit Buah Duku Terhadap Pertumbuhan dan Hasil Tanaman Seledri (Apium graveolens L) Pada Tanah Alluvial - Setia Budi, Subandi Surachman (Fakultas Pertanian Universitas Tanjungpura, 2015)
THE INFLUENCE OF DUKU SKIN COMPOST TO GROWTH AND YIELD OF CELERY (Apium graveolens L) ON ALLUVIAL SOIL Subandi (1), Surachman (2), Setia Budi (2) (1) Students Of Agriculture Faculty (2) The Lecturer Of Agriculture Faculty Of Tanjungpura University Pontianak ABSTRACK This study aims to determine the effect of duku skin compost on growth and yield of celery on Alluvial soil. The research was conducted in Punggur Besar Village, Kubu Raya District. The research was conducted from 14th September 2014 until 09th November 2014. This study used a completely randomized design (CRD), which consists of 6 treatments and 4 replications, each replication consisted of 3 plants so there are 72 plants totally. The treatments used: k0 (without giving duku skin compost), k1 (10% organic matter equal to 22.23 gr/polybag), k2 (15% organic matter equal to 76.73 gr/polybag), k3 (20% organic matter equal to 131.2 gr/polybag), k4 (25% organic matter equal to 185.7 gr/polybag) and K5 (30% organic matter equal to 240.2 gr/polybag). The variables measured were the root volume, number of leaf, plant height, the upper plant fresh weight, and the upper plant dry weight. The results showed that application of duku skin compost on Alluvial gave significant effect on number of leaf, plant height, the upper plant fresh weight, and the upper plant dry weight. Duku skin compost significantly affected all variables observation, with the best results at a 30% of organic matter equal to 240.2 gr/polybag. Keywords: Alluvial, Celery, Duku Skin Compost,